Biosimilars in Pediatric Inflammatory Bowel Diseases: A Systematic Review and Real Life-Based Evidence - Dipasquale, Valeria; Cicala, Giuseppe; Spina, Edoardo; Romano, Claudio (Frontiers in Pharmacology, 2022)
Background: Many pediatric inflammatory bowel disease (IBD) patients are now using biosimilars of anti-tumor necrosis factor-α (TNF-α), with increasing trends in recent years. This study reviewed all available data regarding the use of biosimilars in children with IBD. Methods: PubMed, Google Scholar, Scopus, and CENTRAL databases were searched through keywords; inflammatory bowel diseases, Crohn’s disease, ulcerative colitis, biosimilar and child were combined using “AND” and “OR”. Original research articles involving pediatric patients receiving one of the biosimilar medications based on the anti-TNF-α biologic drugs approved for pediatric IBD treatment, independently from efficacy and drug response, were included. Results: Nine studies were included in the evidence synthesis. CT-P13 was the biosimilar used in all studies. Four studies assessed the induction effectiveness of CT-P13. Clinical response and remission rates of biosimilar treatment were 86%-90% and 67%-68%, respectively, and they were not significantly different to the originator group. Five prospective studies on patients elected to switch from originator IFX to CT-P13 yielded similar results. Adverse events related to CT-P13 were mostly mild. The most frequently reported were upper respiratory tract infections. The switch from the originator had no significant impact on immunogenicity. Conclusion: The current review showed reported CT-P13 effectiveness as measured by clinical response and/or remission rates after induction or during maintenance and suggest that there is no significant difference with that of the originator IFX. Further studies are warranted, including clinical and pharmacovigilance studies.